Effects of GLP-1 Receptor Agonists on Bone Metabolism and Fracture Risk in Type 2 Diabetes and Obesity: Mechanisms and Clinical Evidence — A Narrative Review - Bojanowski, Hubert; Marczak, Zuzanna; Sito, Maksymilian; Jurkowski, Filip; Wójcik, Łukasz; Gawron, Natalia; Dobracka, Aleksandra; Zachar, Kinga; Jarowicz, Monika; Czmyr, Jędrzej (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Type 2 diabetes (T2D) is associated with increased fragility fracture risk despite preserved or elevated bone mineral density (BMD) ("diabetic bone paradox"). As glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are widely used in T2D and obesity, this narrative review synthesizes evidence on their effects on bone turnover, BMD and fracture outcomes, contrasting diabetic and non-diabetic populations. Brief description of the state of knowledge: Preclinical data suggest GLP-1 RAs may promote osteoblastogenesis and reduce marrow adipogenesis (e.g., via Wnt/β-catenin and OPG/RANKL signalling). Clinically, effects appear context-dependent and strongly influenced by weight loss. In T2D, most trials report neutral or small favourable changes in BMD and bone turnover markers. Some meta-analyses report a possible reduction in fractures (notably with longer liraglutide exposure), but fracture events were often secondary/safety endpoints and were not adjudicated, limiting certainty. Summary (conclusions): Overall, current evidence to date suggests no major skeletal safety signal for GLP-1 RAs in T2D, while definitive fracture-prevention effects remain unproven. In obesity, baseline risk assessment and monitoring of bone health should be considered in high-risk individuals, and future studies should prioritize adjudicated fracture endpoints and longer follow-up.